Hábitos alimentarios y su incidencia en la hipoglucemia en embarazadas de 18 – 24 años que acuden a consulta externa en el Hospital Jaime Roldos Aguilera De La Ciudad De Ventanas, durante septiembre 2017 – febrero 2018 - Chila Izquierdo, Luigi Alberto (2018)
Eating habits Metabolic disorders in the human body are the main cause of metabolic disorders such as Hypoglycemia. Poor eating habits and unhealthy lifestyles are the probable cause of around 60% of the diseases suffered by humans. The low diet, prior to pregnancy, as well as excessive weight loss and malnutrition during pregnancy are negative factors that involve complications for the pregnant woman, her fetus and neonate. Likewise, the possession of unhealthy lifestyles are factors closely related to the incidence of Hypoglycemia during pregnancy. To diminish these negative indicators, a diet appropriate to individual needs is necessary, not performing or decreasing physical exercises and maintaining healthy lifestyle habits. Knowing the incidence of Hypoglycaemia in pregnant women aged 18 - 24 years who attend the outpatient clinic in the Jaime Roldós Aguilera Hospital of the City of Windows, during September 2017 - February 2018, is the general objective of this research. To perform this work, we investigated the population or total universe comprising 60 pregnant adolescent women, who attend the outpatient clinic at Jaime Roldós Aguilera Hospital in the city of Ventanas, during September 2017 - February 2018. The results were analyzed statistically and it was concluded that it is necessary to achieve the Edition of a television spot on correct lifestyles and eating habits, to avoid the incidence of Hypoglycemia in adolescent pregnant women and children of childbearing age in the canton of Ventanas.